Penerapan PJBL untuk Meningkatkan Keterampilan Sosial Emosional pada Materi Cahaya dan Alat Optik - Rezwandy Wahyudi Saputra (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Social-emotional skills (SES) are an important aspect that needs to be developed in the learning process. However, in practice, they often receive less attention in science learning activities. This study aims to analyze the improvement of students' social-emotional skills through the implementation of the Project-Based Learning (PjBL) model on the topic of light and optical instruments. The research method used is Classroom Action Research (CAR) based on the John Elliot model, with the research subjects being 33 students of class VIII B at SMPN 3 Sumber. The study was conducted in two cycles, each consisting of three meetings with the stages of planning, action, observation, and reflection. Data were collected through observation and peer assessment. The results showed an increase in the average percentage of SES from 24.7% (Not Yet Developed category) in the pre-cycle to 46.1% (Beginning to Develop category) in cycle 1, and a significant increase to 77.9% (Well Developed category) in cycle 2. The highest improvement occurred in the relationship skills domain, with an increase of 57.1%. This study proves that the implementation of the PjBL model is effective in enhancing students' social-emotional skills and can serve as an alternative learning approach that not only focuses on academic aspects but also on holistic character development.